The Creation of the Performative Theater Ruang Ketubuhan - Galuh Tulus Utama; Riswani Riswani; Fantri Pribadi; Marrisa Aulia Mayangsari; Iga Ayu Intan Candra (Gondang: Jurnal Seni dan Budaya, 2025)
Site-specific performance is established in international practice, yet its application in post-disaster contexts remains under appreciated. This study addresses this gap by exploring the creation of ‘Ruang Ketubuhan’ (The Embodied Space), a performative theater work developed in the ruins of Mount Merapi eruption, Sleman, Yogyakarta, in 2010. Grounded in Practice-as-Research method, site-specific ethnography, and autoethnography, this study documents a creative process where ruins, objects, and borrowed narratives from survivors become active dramaturgical events. The findings demonstrate that the performer’s body functioned as a medium to translate historical trauma into a shared and empathetic experience. It gained through methods of spatial attunement and emotional memory reflection. The study concludes that Ruang Ketubuhan offers a model for ‘embodied site-specificity’ which argued that the interweaving of body, space, and memory in performance constitutes a significant mode of knowledge production. This moves beyond aesthetic documentation to show how performative practice can actively mediate challenging history, making it accessible and relevant for both live and mediated audiences.